PENGARUH KEPUASAN KERJA TERHADAP KINERJA PENGAWAS SEKOLAH DASAR KABUPATEN/KOTA PROPINSI RIAU - Baheram, Murni (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
The objective of this research is to know out effect of job satisfaction on performanceof elementary schools supervisor official / city in Riau province. This research used quantitativeapproach with uses causal survey method by using Path Analisys Technique. The samples of thisresearch were 60 elementary school supervisor selected randomly. In the data were collected byspreading questioner and analyze with correlation by supporting descriptive statistics. The resultof the research on direct positive effect of job satisfaction on performance of elementary schoolssupervisor . The conclusion of the research is direct positive effect of job satisfaction onperformance of job satisfaction elementary schools supervisor. The higher of job satisfaction,the higher of performance of elementary schools supervisor official .On the other side, job ofelementary school supervisor can be increase by job satisfaction.Key words: job satisfaction, Job performance, supervision